An Investigation of the Readiness of the Prakerin Program Implementation to Improve Students’ Competence - Fauziah, Dary Nasmi; Wati, Kurnia; Ibarra, Florante P.; Quicho, Rosario F.; Collantes, Leila M. (Universitas Jambi, Indonesia, 2024)
This research aimed to investigate the readiness of the Prakerin Program implementation to improve students’ competence in selected vocational high schools in Bungo District, Jambi, Indonesia. This research used a descriptive quantitative research design and inferential statistics. The results indicated that the implementation of the Prakerin program acquired well to improve student’s competence. It also showed significant correlations between the readiness of the Prakerin program and student competence from various schools. Specifically, there was a positive significance and a high correlation between the readiness of the Prakerin program implementation and student competence. Investigation of the relationship between the ten sub-components of Prakerin program implementation readiness and student competence revealed that all the ten sub-components correlated with the student competence. Students had a competence by being able to develop themselves and their ability to do practicum.